Sistem Penunjang Keputusan Pemilihan Media Promosi Sekolah Menggunakan Metode MOORA - Rindhani Aditia, Mellya; Dina Ediana; Sayendra Safaria (Jurnal Teknologi Informasi (JUTECH), 2025)
Abstract Effective promotion is a crucial strategy to enhance the competitiveness of private schools amid increasing competition. This study aims to determine the most optimal promotional media for private schools using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method. This method was chosen because it can objectively process multiple criteria in decision-making. The research stages include identifying criteria and promotional media alternatives, assigning weights, constructing the decision matrix, normalizing data, and calculating optimization values using the maximax and minmax approaches. The analyzed alternatives include social media, brochures, billboards, and print media, with criteria such as cost, reach, effectiveness, and ease of access. The analysis results show that social media obtained the highest score and is therefore deemed the most effective promotional media for private schools. These findings are expected to serve as a reference for schools in designing more targeted and efficient promotional strategies.